(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The painting made by the artists demonstrates their enthusiasm to convey their emotions which communicates certain setting of history and contemporary period. It resembles an individual journal of artist wherein the artist registers their torment, enduring, distress with art structures, shading, analogy and increase their own passionate articulation. Singular understandings of environment around them symbolize bland creation to portraying social parody. Their imaginative undertaking to blend Indian and present-day disposition give the work an incredible uniqueness. Important Allegory-All the women artists present a social message using images, codes and illustrations. They like to show the injury and enduring in backhanded way and are fit for connecting with the watcher in their art work. Each image has a reasonable importance, a vehicle for the artist’s self-articulation and uncovers strange parts of their imaginative art venture.